Security enhancement for software defined networking - Cho, Wai Hlaing (2019)
Software defined network (SDN) system is a scheme to introduce new network technology designed to make the network more flexible, agile and automate centralized management of a huge network. SDN can lower the operating cost in terms of error handling, maintenance and robustness against outage through simplifying the network management by integrating the control plane of multiple devices into a one instance. The controller is a brain of SDN system and offers visibility over the whole network. However, the deployments, protocols and controller software are new and the history of SDN attacks is unknown as well. Therefore, it is important to take precautions before deploying an SDN system and secure every possible vulnerable point of the SDN system. Recently many surveys and professionals have identified possible vulnerabilities and potential attack scenarios in SDN system that could impact SDN network in term of availability, integrity, confidentiality and authenticity. In this final year project, various types of security issue in SDN will be analyzed and focused on securing the communication link between controller and data plane devices. A current communication security protocol TLS used in SDN system will be verified using the Scyther Tool. TLS is used for the purpose of securing the transmitted data between controllers and network devices. A suggestion will be proposed to enhance the security of communication channel between controller and network devices in software defined network system and will be proof with Scyther Tool.